Cultural Meanings of Madness and Pathways to Care for People with Mental Disorders in Indonesia: An Anthropological-Psychological Literature Review - tresno (Indonesian Journal of Medical Anthropology, 2026)
This study examines the cultural meanings of mental illness and the diverse healing pathways in Indonesia through an anthropological–psychological perspective. Using Arthur Kleinman’s explanatory model and the concept of moral experience, a qualitative literature review synthesizes ethnographic and psychological studies across Sumatra, Java, Kalimantan, Sulawesi, Bali, and Papua to understand how Indonesian societies interpret and treat madness within their moral worlds. The findings reveal three dominant healing systems. Pasung (physical restraint) operates as a socio-moral mechanism to restore community harmony when madness threatens social order. Ruqyah (Islamic exorcism) represents a spiritual approach that links mental disturbance to sin, weakened faith, or supernatural interference, with healing achieved through Qur’anic recitation and moral purification. Melukat (Balinese purification ritual) reflects a cosmological model in which madness signifies disharmony between humans, nature, and deities, restored through sacred water rituals. Across these practices, madness is conceptualized as a moral and relational disorder rather than a psychological dysfunction, and healing becomes a process of moral restoration that reestablishes equilibrium among self, community, and the sacred. These findings challenge the universality of Western biomedical psychiatry and highlight the need for culturally grounded, ethically sensitive mental health frameworks integrating medical, religious, and customary systems.